Confirmation on the presence of the enigmatic "Machupicchu Arboreal Chinchilla Rat" Cuscomys oblativus (Abrocomidae) - Ochoa, José A. (2020)
New evidence on the presence of the Machupicchu Arboreal Chinchilla Rat (Cuscomys oblativus: Abrocomidae) from Machupicchu Historic Sanctuary are reported, using camera tramps during april 2018 to april 2019. 67 photographic records were obtained in five mountain forest localities between 2842 and 3413 meters of altitude. All the records correspond to adult specimens and present nocturnal habits with more activity from 10 pm to 04 am. At the moment, no records are known of C. oblativus outside the Machupicchu, being one of the three endemic mammal species of the protected natural area.